2020
DOI: 10.2196/18505
|View full text |Cite|
|
Sign up to set email alerts
|

Excessive Smartphone Use and Self-Esteem Among Adults With Internet Gaming Disorder: Quantitative Survey Study

Abstract: Background Smartphone overuse can harm individual health and well-being. Although several studies have explored the relationship between problematic or excessive smartphone use and mental health, much less is known about effects on self-esteem, which is essential in having a healthy life, among adults with mental health disorders, including internet gaming disorder. Furthermore, given that smartphone usage differs by gender, little is known about gender differences in the relationship between smart… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, a multicenter study among Saudi university students showed that female students were more affected [ 18 ]. A study in Korea also reported that excessive use of smartphone and smartphone addiction–proneness is higher among females [ 6 ]. Furthermore, De-Sola Gutierrez et al [ 8 ] reported that all the studies included in their review indicated that women or girls have higher levels of dependence and problematic use than men or boys [ 8 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a multicenter study among Saudi university students showed that female students were more affected [ 18 ]. A study in Korea also reported that excessive use of smartphone and smartphone addiction–proneness is higher among females [ 6 ]. Furthermore, De-Sola Gutierrez et al [ 8 ] reported that all the studies included in their review indicated that women or girls have higher levels of dependence and problematic use than men or boys [ 8 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…They propose moving away from the addiction framework when studying technological behaviors and using, instead, terms such as “problematic use” to describe them [ 2 ]. Nevertheless, excessive and problematic use of smartphone negatively impacts people’s lives, including their self-esteem [ 6 ]. The problematic use of a smartphone can be defined as “an inability to regulate one’s use of the mobile phone, which eventually involves negative consequences in daily life (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased self-esteem plays a role in obsessive-compulsive disorders (Coughtrey et al, 2018), psychosis (Tarrier et al, 2004;Xu et al, 2013). Furthermore, LSE is also related to addictive behaviours (Arsandaux et al, 2020;Kim et al, 2020), and self-harm or suicide attempts (Bhar et al, 2008;Palmer, 2004;Tarrier et al, 2004;Wisman et al, 2015). LSE has been shown to have a significant effect on people's lives, not just in the context of psychopathology, but in a broader sense; for instance, dropping out of school early, teenage pregnancy and poor lifelong employment history (Mann et al, 2004;Waite et al, 2012).…”
Section: Relationship Between Lse and Mental Disordersmentioning
confidence: 99%
“…Revealing the mechanisms that in uence problematic smartphone use is an important prerequisite for reducing the occurrence of this behavior. Problematic smartphone use has been tentatively suggested by researchers to be negatively related to self-esteem [10][11][12]. Self-esteem is a stable personality trait that Rosenberg [13] de ned as a person's overall opinion of their own value.…”
Section: Introductionmentioning
confidence: 99%